The Evaluation of a Selected Part of the Road Network in Zilina Region - Jan Celko; Daniela Durcanska; Jozef Komacka; Eva Holescakova (Communications, 2002)
Two international corridors "Va" and "VI" pass through Žilina region, but yet the road network density of the region belongs to the lowest in Slovakia. The road network is loaded excessively and main arteries come under a section with a maximum accident rate. The model of the communication attendance of the region that has been solved recently deals with the road network in the region in the terms of the transportation system integration. The paper presents basic characteristics of the network, information on the present state of the traffic, as well as principles of a traffic modelling process. The main resources for improving the traffic situation based on the evaluation of present situation and forecast for network loading are presented in the conclusion.